Simultaneous Determination of Three Alkaloids in Wutou Decoction in Rat Plasma Via the UPLC–MS/MS Method and its Application in Pharmacokinetic Study - Jian, WU; Yu-bin, JI; Ying-jie, Liu; Ying, XU; Wei, Zheng; Miao, Yu (Current Pharmaceutical Analysis, 2020)
Introduction: Wutou decoction has been wildly applied for the treatment of RA in China for several thousand years. Methods: This study aims to develop a highly sensitive and specific ultra performance liquid chromatography coupled with tandem mass spectrometry and electrospray ionization (UPLC-ESI-MS/MS) method to explore the pharmacokinetic properties of three representative bioactive alkaloids after intragastric administration of Wutou decoction in rats. Chromatographic separation was performed on a C18 column under the Multiple Reaction Monitoring (MRM) in the positive electrospray ionization (ESI) mode. The pharmacokinetic parameters were evaluated by software DAS 3. 0. Results: The validation of the method was achieved in accordance with the FDA guidelines. The results of pharmacokinetic study showed that the in vivo concentrations of benzoylmesaconine and benzoylhypaconine were significantly higher than benzoylaconine. Our PK results showed that these three compounds were quickly absorbed after the administration of Wutou decoction, and Tmax ranged from 30 min to 45 min. Conclusion: The results of pharmacokinetic study showed that the in vivo concentrations of benzoylmesaconine and benzoylhypaconine were significantly higher than benzoylaconine. There were also similar pharmacokinetic behaviors observed among BAC, BHA, and BMA after oral administration of WTD.
Keywords: Pharmacokinetic